Skeletal muscle major histocompatibility complex class I and II expression differences in adult and juvenile dermatomyositis - Samuel Katsuyuki Shinjo; Adriana Maluf Elias Sallum; Clovis Artur Silva; Suely Kazue Nagahashi Marie (Clinics, 2012)
OBJECTIVE: To analyze major histocompatibility complex expression in the muscle fibers of juvenile and adult dermatomyositis. METHOD: In total, 28 untreated adult dermatomyositis patients, 28 juvenile dermatomyositis patients (Bohan and Peter's criteria) and a control group consisting of four dystrophic and five Pompe's disease patients were analyzed. Routine histological and immunohistochemical (major histocompatibility complex I and II, StreptoABComplex/HRP, Dakopatts) analyses were performed on serial frozen muscle sections. Inflammatory cells, fiber damage, perifascicular atrophy and increased connective tissue were analyzed relative to the expression of major histocompatibility complexes I and II, which were assessed as negatively or positively stained fibers in 10 fields (200X). RESULTS: The mean ages at disease onset were 42.0±15.9 and 7.3±3.4 years in adult and juvenile dermatomyositis, respectively, and the symptom durations before muscle biopsy were similar in both groups. No significant differences were observed regarding gender, ethnicity and frequency of organ involvement, except for higher creatine kinase and lactate dehydrogenase levels in adult dermatomyositis (p<0.050). Moreover, a significantly higher frequency of major histocompatibility complex I (96.4% vs. 50.0%, p<0.001) compared with major histocompatibility complex II expression (14.3% vs. 53.6%, p=0.004) was observed in juvenile dermatomyositis. Fiber damage (p=0.006) and increased connective tissue (p<0.001) were significantly higher in adult dermatomyositis compared with the presence of perifascicular atrophy (p<0.001). The results of the histochemical and histological data did not correlate with the demographic data or with the clinical and laboratory features. CONCLUSION: The overexpression of major histocompatibility complex I was an important finding for the diagnosis of both groups, particularly for juvenile dermatomyositis, whereas there was lower levels of expression of major histocompatibility complex II than major histocompatibility complex I. This finding was particularly apparent in juvenile dermatomyositis.